SPARC Data Initiative: Comparison of water vapor climatologies from international satellite limb sounders. Issue 20 (21st October 2013) - Hegglin, M. I.; Tegtmeier, S.; Anderson, J.; Froidevaux, L.; Fuller, R.; Funke, B.; Jones, A.; Lingenfelser, G.; Lumpe, J.; Pendlebury, D.; Remsberg, E.; Rozanov, A.; et al.
<x xml:space="preserve">Abstract</x> [1] Within the SPARC Data Initiative, the first comprehensive assessment of the quality of 13 water vapor products from 11 limb‐viewing satellite instruments (LIMS, SAGE II, UARS‐MLS, HALOE, POAM III, SMR, SAGE III, MIPAS, SCIAMACHY, ACE‐FTS, and Aura‐MLS) obtained within the time period 1978–2010 has been performed. Each instrument's water vapor profile measurements were compiled into monthly zonal mean time series on a common latitude‐pressure grid. These time series serve as basis for the "climatological" validation approach used within the project. The evaluations include comparisons of monthly or annual zonal mean cross sections and seasonal cycles in the tropical and extratropical upper troposphere and lower stratosphere averaged over one or more years, comparisons of interannual variability, and a study of the time evolution of physical features in water vapor such as the tropical tape recorder and polar vortex dehydration. Our knowledge of the atmospheric mean state in water vapor is best in the lower and middle stratosphere of the tropics and midlatitudes, with a relative uncertainty of ±2–6% (as quantified by the standard deviation of the instruments' multiannual means). The uncertainty increases toward the polar regions (±10–15%), the mesosphere (±15%), and the upper troposphere/lower stratosphere below 100 hPa (±30–50%), where sampling issues add uncertainty due to large gradients and high natural variability in water vapor. The minimum found in multiannual (1998–2008) mean water vapor in the tropical lower stratosphere is 3.5 ppmv (±14%), with slightly larger uncertainties for monthly mean values. The frequently used HALOE water vapor data set shows consistently lower values than most other data sets throughout the atmosphere, with increasing deviations from the multi‐instrument mean below 100 hPa in both the tropics and extratropics. The knowledge gained from these comparisons and regarding the quality of the individual data sets in different regions of the atmosphere will help to improve model‐measurement comparisons (e.g., for diagnostics such as the tropical tape recorder or seasonal cycles), data merging activities, and studies of climate variability.